Estudo de ancestralidade da população atendida na Fundação Alfredo da Matta - Noronha, Ariani Batista (2019)
Despite being a millennial disease, leprosy still affects a large number of people around the world, and its cause is still being studied, as it is known that multiple factors are related to its outcome. Social and genetic aspects are slightly intrigued to illness, in addition to a range of genes that are investigated related to the development of this pathology. Genetic association studies are extremely important in the response of the disease mechanism, so they need to be as reliable as possible. It is known that there is a set of information that may cause bias in these studies or even lead to false positive results. Analyzes involving these covariates, such as age, sex and ancestry, need to be corrected and repaired by statistical models. It is known that the Brazilian population is described as a heterogeneous group, with ancestral characteristics reflected by the process of colonization that occurred in Brazil, among Europeans, Indians and Africans. Due to this plurality in society, the ideal is to perform the ancestral analysis of each individual involved in the study, through molecular techniques such as fragment genotyping. Using a panel of 46 informational ancestry markers (AIMS), of the Indel (insertion / deletion) type, all autosomal, the present study aimed to estimate ancestry in a sample composed of 1,363 participants from a genetic association case / control study for leprosy, carried out at Fundação Alfredo da Matta (FUAM). In this way, it was possible to describe the ancestral profile of the resident population of Manaus, being the largest survey of ancestry ever performed in the Amazonian population and related to self-reported ethnic-racial information. The population analyzed showed typical ancestral characteristics of mixed populations, with significant proportions of European (EUR), Amerindian (NAM) and African (AFR) ancestry. The 1363 individuals were divided into two groups: cases (422) and controls (941) and showed very similar ancestry indexes in the case group (EUR: 37%, NAM: 36% and AFR: 27%) and in the control group EUR: 36%, NAM: 39% and AFR: 25%), showing that they are homogeneous groups. The association of self-reported ethnicity, when compared with genetic ancestry, showed a relationship in all groups, with the exception of individuals declared black. The data described in this work confirm that the population (cases and controls) used in the genetic association studies at FUAM have ideal and reliable characteristics to be used in this type of sample design without generating bias or spurious associations. Keywords: Ancestry, Manaus, AIMS, Indel, leprosy.